The Effect of Work Culture and Competence Through Job Satisfaction on Employee Performance - Rustan Ali; Irawati Nur; Megawati Beddu; Hartati Hartati; Ulfa Natsir; Anastasia D'ornay (International Journal of Artificial Intelligence Research, 2022)
This study was conducted with the aim to determine and analyze the effect of work culture and competence on job satisfaction and employee performance, analyze the effect of job satisfaction on employee performance, and analyze the effect of work culture and competence on employee performance through job satisfaction at PT. Pelabuhan Indonesia (Persero) Regional IV Makassar. To apply these objectives, data collection techniques are used through observation and questionnaires, while data analysis techniques use research instrument tests, classical assumption tests, path analysis and hypothesis testing. The results showed that work culture and competence had a positive and significant effect on job satisfaction. Work culture and competence have a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance, and the results of the mediation test with the sobel test that job satisfaction can mediate the effect of work culture and competence on employee performance at PT. Pelabuhan Indonesia (Persero) Regional IV Makassar.